PENGARUH PENAMBAHAN ENZIM HIDROLITIK PEPAYA MATANG PADA PAKAN KOMERSIAL TERHADAP PERTUMBUHAN IKAN MAS CANGKRINGAN (Cyprinus carpio L, 1758) - , STEVEN SITONGAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Application of enzyme addition on the feed today used for efforts to increase cultivation. Utilization of ripe papaya as a hydrolytic enzyme in the form of the product \"EZ-Plus\" is added to the commercial feed. This study was to determine the effect of hydrolytic enzymes ripe papaya on commercial diets on growth, feed conversion ratio (FCR), and survival rate (SR) of Cangkringan carp (Cyprinus carpio L, 1758). This study used a completely randomized design (CRD) with 6 treatments and 3 replications, namely the addition of \"EZ-Plus\" into the feed with a protein content of 25%, 32%, 40%. Control treatment is without the addition of feed enzymes. Dose addition of \"EZ-Plus\" as much as 5g diluted with 1 L of water. Then 50 ml of solution was sprayed on 1 kg of feed. Analysis of the data using analysis of variance (one-way ANOVA), if there is a significant difference analysis followed by DMRT (Duncan's Multiple Range Test) to determine the significant difference between treatments. The results showed that 40% of the control treatment had the highest daily growth rate and significant difference with other treatments, the total value of the average growth in weight and body length of 36.83 g ± 6.18 and 6.05 ± 0.97 cm. While growth in the other feeds besides to control 40% have a uniform value. Daily length growth rate have uniform result between 6 treatments. The highest FCR was 1.215 ± 0.04 was obtained control of 40%, while 5 other treatments have a uniform value. SR on days 0-30 for all treatments reached 100%, at day 45-75 SR values fall in the range of 9.1% -24.1%. Thus, the conclusion of this research is the application of papaya hydrolytic enzymes in the commercial feed as many as 50 ml / kg of mixing 5g papaya enzyme extract with 1 L of water is not positively correlated with the growth parameters of body weight, body length, and FCR of Cangkringan carp.